Implementasi E-Learning Media Pembelajaran Berbasis Website Menggunakan Articulate Storyline dalam Mata Pelajaran DKV - Ramdani, Anggi; Setiawan, Dena Latif (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Blended Learning method using Chromebook-based Quizizz learning media on the learning outcomes of fifth-grade students in Indonesian language subjects at SDN Cilimusari. The background of this study is based on the low learning outcomes of students and the lack of variety in engaging learning media. The research uses a quantitative method with a One Group Pretest-Posttest Design. The research subjects consisted of 17 fifth-grade students. The research instrument was a multiple-choice test consisting of 20 items that had undergone validity testing. The data were analyzed using validity tests, normality tests, and hypothesis tests. The research results show a significant increase in student learning outcomes after the implementation of the Blended Learning method based on Quizizz through Chromebook devices. The average posttest score was higher compared to the pretest, thus the alternative hypothesis (Ha) was accepted. In conclusion, the implementation of the Blended Learning method using Quizizz media positively and significantly affects the improvement of students' Indonesian language learning outcomes. This learning model also enhances students' motivation, engagement, and interest in learning.